Beyond the Lab: Influencing Practice and Policy. (January 2020) - Hetland, Lois; Sheridan, Kimberly; Veenema, Shirley
In this article, the authors describe over 20 years of work with Ellen Winner at Project Zero, a research and development group at the Harvard Graduate School of Education. This included a cross-arts curriculum and assessment project aimed at practitioners (ArtsPROPEL, 1989–1995), 10 meta-analytic syntheses of the effects of arts learning on nonarts achievement (REAP, 1997–2001), and an observational theory-building study of the dispositions intended to be learned in high school art classes and the structures through which they are taught, meant for audiences of both practice and theory (Studio Thinking, 2001–2013). Ellen's perspective as an experimental psychologist interacted with ours in fertile ways to make richly rewarding collaborations in our efforts to make sense of art education practices. From how she chooses what she studies, to her eclectic approaches to research, to addressing her work to broad audiences, psychologists have much to gain from Ellen's methods.